Experimental and mathematical modeling of hindered diffusion effect of cationic dye in the adsorption onto bentonite. Issue 1 (February 2019) - Souza, P.R.; Dotto, G.L.; Salau, N.P.G.
Highlights: Adsorption of methylene blue onto bentonite was interpret by diffusional mass transfer models. The molecular size of the methylene blue was very close to the basal space of the bentonite. The inclusion of hindered diffusion in PVSDM model allows an improvement of the fitting accuracy of experimental data. The adsorption mechanism is controlled by intraparticle diffusion. Superficial diffusion contributed with 80%, whereas pore volume diffusion contributed with 20% of the intraparticle diffusion. Abstract: Adsorption of cationic dye (methylene blue) onto bentonite was interpret by diffusional mass transfer models. It was mainly observed that the hindered diffusion effect may be considered in the adsorption of methylene blue dye, which consisted of steric and drag effects and obstruction by molecules adsorbed on the pore walls. It has also been shown that this extra resistance occurred because the molecular size of the methylene blue was very close to the basal space of the bentonite. Finally, the Biot number indicates that the adsorption mechanism is controlled by intraparticle diffusion, which 20% occur due to diffusion in pore volume and 80% due to surface diffusion.